2022
DOI: 10.1055/s-0042-1749206
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da COVID-19 no momento de reparo do manguito rotador e método de acompanhamento pós-operatório

Abstract: Resumo Objetivo O reparo do manguito rotador (RMR) é um dos procedimentos artroscópicos mais comuns. Nossa pesquisa visa quantificar o impacto da pandemia de COVID-19 sobre o RMR, especificamente em pacientes com lesões agudas e traumáticas. Métodos Os prontuários institucionais foram consultados para identificação de pacientes submetidos ao RMR artroscópico entre 1° de março e 31 de outubro de 2019 e de 2020. Dados demográficos, pré-operatórios, perioperatórios e pós-operatórios dos pacien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While the trend did not approach significance, it is still noteworthy that approximately 10% of patients did not pur- sue the standard of care protocol following an arthroscopic RCR. Despite this difference, Wang et al did not report a significant difference in the incidence of complications, unplanned readmissions, or revisions between their 2020 and 2019 cohorts (Wang et al 2022). Similarly to Wang et.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…While the trend did not approach significance, it is still noteworthy that approximately 10% of patients did not pur- sue the standard of care protocol following an arthroscopic RCR. Despite this difference, Wang et al did not report a significant difference in the incidence of complications, unplanned readmissions, or revisions between their 2020 and 2019 cohorts (Wang et al 2022). Similarly to Wang et.…”
Section: Discussionmentioning
confidence: 91%
“…Due to a shift in focus on emergent care, physical therapy became much less accessible for many patients. Previous studies reporting on this have suggested that the delays in care did not lead to significant differences in range of motion or patient-reported outcomes (Wang et al 2022;Smith et al 2022). We sought to investigate delays or interruptions in physical therapy that led to adverse outcomes at our tertiary care medical center.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations